PENGARUH VOLUME PENJUALAN DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PRODUK MAKANAN DAN MINUMAN YANG BERLABEL HALAL DI INDONESIA PERIODE 2014-2018 (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ) - Hikmah, Rima Nurul; Aulia, Ismiani; Nopianti, Risma; Sari, Ristiani Kartika (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2020)
The study aims to determine the effect of sales volume and operational costs to the netincome in the food and beverage companies listed on the BEI 2014 -2018 amounted 16companies. The sampling technique used in this research is purposive sampling and based ontechnique the sample who have qualifications is 7 companies with 5 years period (2014-2018)so the number was analysis is 35 samples. The analysis method used is multiple linearregression analysis and for hypothesis used t test and f test by using software SPSS version 22.The result of the research show that (1) sales volume has positive effect on the net income (2)operational cost has not effect on the net income (3) sales volume and operational cost affectto net income simultaneously.Keywords : Sales Volume, Operational Costs, Net Profit